Perencanaan Pembelajaran IPA yang Interaktif dalam Menumbuhkan Minat Belajar Siswa Kelas XII SMAN 9 Pekanbaru - Verlia Agustin; Willyansah Willyansah (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
This article provides an explanation of how interactive learning can improve students’learning request in class XII SMAN 9 Pekanbaru. Interactive learning in it’s application allows students to participate in learning, actively ask questions, raise students’curiosity and enthusiasm in focusing on learning materials. These things are an indicator that can be seen that with the existence of interactive learning can increase their willingness to learn, student interest in learning. This article presents the implementation of learning by using interactive media properly and correctly, along with examples of interactive learning that can be utilised by teachers in teaching and learning activities. All data obtained in this article is based on the result of observations and interviews conducted at SMAN 9 Pekanbaru. It is hoped that this interactive learning can foster a sense of students interest in learning and also satisfactory cognitive learning outcomes.